Strategies to Cope with Phases of Spiritual Dryness in Seventh-Day Adventists - Büssing, Arndt (Journal of religion and health, 2021)
In Adventists (n = 603) 45% were less effective and 55% more effective in coping with phases of spiritual dryness, particularly those with leading roles in the church. Strategies such as devotion/trust in God, private prayer/meditation/scripture reading, openness, talks with close others, and self-care were most often utilized. Their ability to cope was predicted best by low Acedia, Living from the Faith, low emotional exhaustion, well-being and having a duty in the church (R2 = .24). When these phases were overcome, several perceived spiritual depth and were able to help others all the more. Helpful strategies should be made available to support persons struggling with spiritual dryness.